Composite catalyst and process for preparing acrylic resin retanning agent by using same
By using the metal catalysts, ZSM-5 molecular sieves and other components in the composite catalyst, adjust the aggregation reaction of acrylic resin tanner, solve the problem of excessive aggregation or premature cross-linking. Essence
Patent Information
- Application Number
- CN202411907956.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Acrylic resin tanning agents are prone to overpolymerization or premature cross-linking during the preparation process, which affects the polymerization reaction and curing quality of the resin.
A composite catalyst, which includes metal catalysts of cobalt salt or copper salt, ZSM-5 molecular sieve, hydrogen peroxide, cross-linking agents and collaborative promoters. Through the synergy of these ingredients , Avoid excessive aggregation or premature cross -linking.
Effectively promote the cluster reaction of acrylic, methyl acrylic, and acrylamide, improve the structural uniformity and cross -linking of the final polymer, and ensure that the acrylic resin resin resin -reopening agent has a good resuscitation performance.
Smart Images

Figure CN119350535A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation and application of composite catalysts, and in particular to a composite catalyst and a process for preparing an acrylic resin retanning agent using the composite catalyst. Background Art
[0002] Retanning is an important process in the modern leather industry and is known as the "alchemy" in leather processing. With the continuous development of the leather industry, people are increasingly aware of the importance of retanning in the leather process, especially the retanning of light leather, which plays a decisive role in improving the quality of leather and increasing the variety of patterns and colors. Today's consumer demand for high-end leather products has increased dramatically, and the performance of leather products of different grades, tastes and patterns mainly depends on the retanning process. Therefore, Japanese leather expert Ogihara Nagaichi called retanning "the lifeline of the tannery." The quality of the retanning effect directly depends on the quality of the retanning agent, and the importance of the retanning agent is obvious.
[0003] Acrylic resin tanning agent is a homopolymer of (meth) acrylic acid, or a copolymer of acrylic acid monomer and other vinyl monomers. It is an important class of leather chemical materials. In addition to giving leather excellent chemical and physical properties, it also has a very competitive price-performance ratio. Since acrylic resin tanning agents have stable chemical properties and are environmentally friendly during the application process, and more importantly, they have high absorption for mineral tanned leather, especially chrome tanned leather, they play an important role in the retanning of chrome tanned leather.
[0004] The performance of acrylic resin tanning agents depends largely on the selection and molecular weight of monomers. Due to the diversity of monomer selection, acrylic resin tanning agents now have a variety of different series of products, and the applications of various products in leather making are also different. At the same time, due to the many advantages of acrylic resin tanning agents, such as abundant sources of synthetic raw materials, flexible molecular design, and mature preparation technology, they are still widely used in the leather industry for a long time. At present, acrylic resin tanning agents are mainly used in pre-tanning, chrome tanning, retanning of chrome tanned leather, manufacturing of waterproof leather / washable leather, and combined with other tanning agents to manufacture chrome-free tanned leather.
[0005] During the preparation of acrylic resin tanning agents, acrylic monomers tend to self-polymerize at high temperatures to form particles or flocs, which affect the polymerization reaction of the resin, and cause incomplete resin curing, color changes, or abnormal odors. Summary of the invention
[0006] The present invention aims at the deficiencies in the prior art, provides a composite catalyst and a process for preparing an acrylic resin retanning agent using the composite catalyst, provides a specific interaction between a metal catalyst using a cobalt salt or a copper salt and a monomer, and in the composite catalyst, uses a ZSM-5 molecular sieve to avoid overpolymerization or premature crosslinking in the copolymerization reaction of acrylic monomers, thereby enhancing the selectivity of the polymerization reaction and reducing the occurrence of side reactions.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A composite catalyst, the main components of the composite catalyst comprising: A metal catalyst, accounting for 5-15% of the mass of the composite catalyst, wherein the metal catalyst is at least one of a cobalt salt and a copper salt; Molecular sieves, accounting for 20-40% of the composite catalyst mass; Hydrogen peroxide, accounting for 5-15% of the mass of the composite catalyst, acts as an oxidant to provide a source of free radicals; Cross-linking agent, accounting for 10-30% of the composite catalyst mass; Synergistic promoter, accounting for 10-20% of the mass of the composite catalyst.
[0008] Preferably, the molecular sieve is a ZSM-5 molecular sieve, and its particle size is 1 nm to 5 nm.
[0009] Preferably, the cobalt salt is cobalt chloride, and the copper salt is copper chloride.
[0010] Preferably, the cross-linking agent is trivinyl triazine, and the synergistic accelerator is one of aluminum fluoride or ammonium bicarbonate.
[0011] Preferably, the preparation process of the composite catalyst comprises the following steps: Step 1: Dissolve cobalt salt or copper salt in an appropriate amount of water, stir evenly, add hydrogen peroxide, and control the temperature of the solution at 30-40°C while stirring; Step 2: Add molecular sieves to the solution and continue stirring to mix the molecular sieves evenly; Step 3: Slowly add the crosslinking agent to the solution and stir evenly; Step 4: adding a synergist to the solution; Step 5: heating the composite catalyst solution to 60-70° C. to activate the active sites of the catalyst; Step 6: Store the activated composite catalyst solution in a dry environment and under refrigerated conditions.
[0012] A process for preparing an acrylic resin retanning agent using a composite catalyst comprises the following steps: Step 1: Prepare a monomer solution by mixing acrylic acid, methacrylic acid and acrylamide monomers in proportion, and add an appropriate amount of water to the mixed solution; Step 2: adding the prepared composite catalyst to the monomer solution; Step 3: heating the reaction solution to 60-70°C and carrying out polymerization reaction under stirring, the reaction temperature is controlled below 90°C, and the reaction time is about 4 hours; Step 4: After the polymerization is completed, cool down to 40°C, add 30% sodium hydroxide solution for neutralization reaction, and adjust the pH value to 6.5-7.0.
[0013] Preferably, in step 1, the ratio of acrylic acid, methacrylic acid and acrylamide monomers is: 60-70% acrylic acid, 20-30% methacrylic acid and 10-20% acrylamide.
[0014] Preferably, in step 2, the added amount of the composite catalyst is 0.5%-2% of the monomer mass.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a composite catalyst and a process for preparing an acrylic resin retanning agent using the composite catalyst, and provides a specific interaction between a metal catalyst using a cobalt salt or a copper salt and a monomer. In the composite catalyst, a ZSM-5 molecular sieve is used to avoid overpolymerization or premature crosslinking in the copolymerization reaction of acrylic monomers, thereby enhancing the selectivity of the polymerization reaction and reducing the occurrence of side reactions.
[0016] The composite catalyst of the present invention can effectively promote the copolymerization reaction of acrylic acid, methacrylic acid and acrylamide by adjusting the proportion and selection of its components, and at the same time improve the structural uniformity and crosslinking degree of the final polymer. The synergistic effect of the crosslinking agent, the metal catalyst and the molecular sieve enhances the selectivity and efficiency of the polymerization reaction, ensuring that the polyacrylic acid resin has good retanning performance.
[0017] The composite catalyst of the present invention fully considers the special reaction properties and polymerization characteristics of acrylic acid, methacrylic acid and acrylamide monomers during research and development, and realizes precise control and optimization of the polymerization reaction by selectively adding metal catalysts, molecular sieves, crosslinking agents and hydrogen peroxide and other components. The synergistic effect of these catalytic components in the reaction makes the composite catalyst particularly suitable for the copolymerization reaction of acrylic acid monomers, and can effectively improve the efficiency and selectivity of the polymerization reaction and the performance of the final polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The composite catalyst preparation process flow chart of the present invention; Figure 2 The present invention is a process flow chart for preparing the acrylic resin retanning agent. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below with reference to the accompanying drawings.
[0021] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be used for other embodiments, variations, improvements, equivalents, and other technical solutions that do not deviate from the spirit and scope of the present invention.
[0022] See also Figure 1 The present invention provides a composite catalyst, the main components of which include a metal catalyst, a molecular sieve, a cross-linking agent and other synergistic promoters. The following is a specific formula of the composite catalyst: Metal catalyst: 5-15% of the mass of the composite catalyst. The metal catalyst is at least one of cobalt salt and copper salt. Cobalt chloride ( ) or copper chloride ( ), which can promote the generation of free radicals in the polymerization reaction and accelerate the reaction process.
[0023] Molecular sieve (ZSM-5): accounting for 20-40% of the mass of the composite catalyst, the particle size of ZSM-5 molecular sieve is 1nm to 5nm. It has an excellent pore structure and can be used as a carrier of the catalyst. At the same time, it can adjust the microenvironment of the reactants and improve the selectivity and uniformity of the polymerization reaction.
[0024] Hydrogen peroxide ( ): accounting for 5-15% of the mass of the composite catalyst. Hydrogen peroxide, as an oxidant, can provide a source of free radicals and promote the initiation of the polymerization reaction. The concentration of hydrogen peroxide should be adjusted as needed to ensure appropriate free radical generation.
[0025] Cross-linking agent (TEVT): accounting for 10-30% of the mass of the composite catalyst, the cross-linking agent is trivinyl triazine, which is used to increase the cross-linking density of the polymer and improve the structural strength and durability of the final polymer.
[0026] Synergistic promoter: accounting for 10-20% of the mass of the composite catalyst, the synergistic promoter is one of aluminum fluoride or ammonium bicarbonate, which helps to activate the active sites of the catalyst and enhance the catalytic effect, especially to improve the initial rate of the reaction and the uniformity of the final polymer.
[0027] Further, the preparation process of the composite catalyst comprises the following steps: Step 1: Dissolve cobalt salt (cobalt chloride) or copper salt (copper chloride) in an appropriate amount of water, stir evenly, add hydrogen peroxide to the solution, and control the temperature of the solution at 30-40°C while stirring to ensure that the hydrogen peroxide is fully dissolved to avoid its premature decomposition; Step 2: Add ZSM-5 molecular sieve to the solution and continue stirring to mix the molecular sieve evenly; the molecular sieve not only serves as a catalyst carrier, but also can adjust the reaction environment and improve the uniformity of the polymerization reaction; Step 3: Slowly add the crosslinking agent trivinyl triazine to the solution and stir evenly; the timing of adding the crosslinking agent is very critical, and it should be added after the catalyst system is fully mixed to ensure uniform distribution of the crosslinking agent; Step 4: Adding a synergistic promoter, i.e., aluminum fluoride or ammonium bicarbonate, to the solution; the function of these co-catalysts is to activate the active sites of the catalyst and enhance the initial rate of the polymerization reaction; Step 5: Heat the composite catalyst solution to 60-70°C to activate the active sites of the catalyst; the activation process enhances the chemical activity of the metal catalyst and the molecular sieve by heating, so that they have sufficient catalytic ability; Step 6: The activated composite catalyst solution should be stored in a dry environment and under refrigerated conditions (4°C) to avoid catalyst inactivation; the catalyst can be taken in appropriate amounts as needed when in use. Example 1
[0028] Step 1: Dissolve 10 g of cobalt chloride in 50 mL of water, stir evenly, add 15 g of hydrogen peroxide, and control the temperature of the solution at 35 ° C and stir; Step 2: Add 30 g of ZSM-5 molecular sieve with a particle size of 1 nm to 5 nm and continue stirring until uniform; Step 3: Slowly add 20g of cross-linking agent and continue stirring; Step 4: Add 20g of synergist; Step 5: Heat to 65°C to activate active sites; Step 6: Store in a dry, refrigerated environment. Example 2
[0029] Step 1: Dissolve 5 g of copper chloride in 50 mL of water, stir evenly, add 15 g of hydrogen peroxide, and control the temperature of the solution at 35 ° C and stir; Step 2: Add 30 g of ZSM-5 molecular sieve with a particle size of 1 nm to 5 nm and continue stirring until uniform; Step 3: Slowly add 20g of cross-linking agent and continue stirring; Step 4: Add 20g of synergist; Step 5: Heat to 65°C to activate active sites; Step 6: Store in a dry, refrigerated environment.
[0030] The present application adopts cobalt salt and copper salt as metal catalysts to prepare composite catalyst.
[0031] See also Figure 1 The present invention discloses a process for preparing an acrylic resin retanning agent using a composite catalyst, comprising the following steps: Step 1: Prepare a monomer solution by mixing acrylic acid, methacrylic acid and acrylamide monomers in proportion, and add an appropriate amount of water to the mixed solution; Step 2: adding the prepared composite catalyst to the monomer solution; Step 3: heating the reaction solution to 60-70°C and carrying out polymerization reaction under stirring, the reaction temperature is controlled below 90°C, and the reaction time is about 4 hours; Step 4: After the polymerization is completed, cool down to 40°C, add 30% sodium hydroxide solution for neutralization reaction, and adjust the pH value to 6.5-7.0. Example 3
[0032] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 4
[0033] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 70°C and stir for 4 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 5
[0034] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 80°C and stir for 4 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 6
[0035] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 90°C and stir for 4 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 7
[0036] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 70%: 20%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 8
[0037] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 60%: 30%: 20%, add to a reactor and add appropriate amount of water to mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 9
[0038] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 2% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Example 10
[0039] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 0.5% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 7.0, adjust the solid content to 28%, and obtain a retanning agent. Embodiment 11
[0040] Step 1: Mix acrylic acid, methacrylic acid, and acrylamide monomers in the following ratio: 65%: 25%: 10%, add them into a reactor, add an appropriate amount of water and mix, to prepare a monomer solution; Step 2: Add the prepared composite catalyst to the monomer solution, the composite catalyst accounting for 1% of the monomer mass; Step 3: Heat the reaction solution to 60°C and stir for 5 hours; Step 4: After the polymerization is completed, cool to 40°C, add 30% sodium hydroxide solution for neutralization reaction, adjust the pH value to 6.5, adjust the solid content to 28%, and obtain a retanning agent.
[0041] In the above-mentioned Examples 3-11 of the present application, the polymerization reaction process of acrylic acid, methacrylic acid and acrylamide monomers is described, and each Example has some differences in reaction conditions or raw material ratios. Among them, in the step of preparing the retanning agent in Examples 3-11, the composite catalyst prepared by any method of Examples 1 and 2 is randomly selected.
[0042] The specific differences are as follows: Example 3-6 provides mixing acrylic acid, methacrylic acid, and acrylamide monomers at different temperatures to prepare a monomer solution; Embodiments 3, 7, and 8 provide for preparing a monomer solution by mixing acrylic acid, methacrylic acid, and acrylamide monomers in different proportions; Examples 3, 9 and 10 provide the preparation of retanning agents by reacting composite catalysts of different masses; Embodiments 3 and 11 provide methods for preparing retanning agents by adjusting pH values to different values.
[0043] The retanning agent prepared under the conditions of Example 3-11 was tested in terms of appearance, effective ingredients, pH value, ionic type and other indicators: The ratio of acrylic acid, methacrylic acid and acrylamide monomers is: acrylic acid 60-70%, methacrylic acid 20-30%, acrylamide 10-20%; the amount of composite catalyst added is 0.5%-2% of the monomer mass; when the polymerization temperature is lower than 90°C, the retanning agent is a transparent, viscous, light yellow liquid with a pH value of about 6.0-7.0, an effective component of 40±1%, and anionic. It has excellent foaming and filling effects.
[0044] The retanning agent of Example 3-11 was further subjected to chemical testing. The experimental table of the composite catalyst for preparing acrylic resin retanning agent products is as follows: Example Composite Catalyst Catalyst dosage (g) Reaction temperature (°C) Reaction time (h) Acrylic acid dosage (g) Crosslinking degree (%) By-product content (%) Remark 3 Taken from Example 1 2 60 5 200 85 1.5 No obvious side effects 4 Taken from Example 2 2 70 4 200 92 1.2 High degree of cross-linking and stable product performance 5 Taken from Example 1+2 1+1 80 4 200 95 1.0 High degree of cross-linking, rapid cross-linking reaction 6 Taken from Example 1 2 90 4 200 80 2.1 High degree of cross-linking, but the reaction is difficult to control 7 Taken from Example 2 2 60 5 200 85 1.0 The degree of cross-linking is extremely high, and the product is relatively hard 8 Taken from Example 1 2 60 5 200 87 2.0 The cross-linking reaction is rapid. 9 Taken from Example 1+2 2+2 60 5 200 85 1.8 High degree of cross-linking, but the reaction is difficult to control 10 Taken from Example 1 2 60 5 200 92 1.2 No obvious side effects 11 Taken from Example 2 2 60 5 200 88 1.6 High product transparency Therefore, the composite catalyst of the present application can avoid over-polymerization or premature cross-linking in the copolymerization reaction of acrylic monomers, enhance the selectivity of the polymerization reaction, improve the degree of cross-linking, and reduce the occurrence of side reactions.
[0045] It should be noted that when the composite catalyst made of metal catalyst (cobalt salt or copper salt) is used in the preparation of retanning agent, acrylic acid, methacrylic acid and acrylamide and other acrylic monomers have certain polarity and reactivity in copolymerization reaction, and their hydrophilicity is strong, and they are easy to react with metal ions or metal salts. In particular, cobalt salt (cobalt chloride) or copper salt (copper chloride) has strong affinity and can form coordination bonds with active groups (such as carboxyl and amide groups) in these monomers. This process can promote the polymerization reaction of monomers, increase the reaction rate and selectivity, and optimize the molecular structure of polymers.
[0046] It should be noted that in the composite catalyst of the present application, molecular sieve (ZSM-5) is used. This material with a unique pore structure plays multiple roles in the copolymerization reaction of acrylic acid monomers: Pore structure of molecular sieve: Molecular sieves such as ZSM-5 have microporous and mesoporous structures, which can control the molecular weight distribution and structure of polymers through physical adsorption or restriction effects. Especially in the polymerization reaction of highly hydrophilic monomers such as acrylic acid and methacrylic acid, molecular sieves can play a role similar to "template", guiding the growth of polymer chains and avoiding over-polymerization or premature cross-linking.
[0047] Enhance reaction selectivity: Molecular sieves can enhance the selectivity of polymerization reactions and reduce the occurrence of side reactions by adjusting the local concentration of monomers and the reaction environment.
[0048] Furthermore, the crosslinking agent such as trivinyl triazine of the present application can react with the free radicals generated in the acrylic acid, methacrylic acid and acrylamide polymers to enhance the crosslinking degree of the polymers and improve their physical and chemical properties. This crosslinking effect complements the synergistic effect of the metal salt and molecular sieve in the composite catalyst, thereby improving the overall performance of the retanning agent.
[0049] Acrylic monomers (such as acrylic acid and methacrylic acid) have high reactivity to free radicals. Hydrogen peroxide, as an initiator, can efficiently generate free radicals in the polymerization reaction and promote the polymerization reaction of the monomers. Combined with the synergistic effect of metal catalysts and molecular sieves, the reaction rate and the molecular structure of the polymer can be effectively adjusted.
[0050] The special reaction properties and polymerization characteristics of acrylic acid, methacrylic acid and acrylamide monomers were fully considered during the research and development of this composite catalyst. By selectively adding metal catalysts, molecular sieves, cross-linking agents and hydrogen peroxide, precise control and optimization of the polymerization reaction were achieved. The synergistic effect of these catalytic components in the reaction makes this composite catalyst particularly suitable for the copolymerization of acrylic acid monomers, and can effectively improve the efficiency and selectivity of the polymerization reaction and the performance of the final polymer.
[0051] Those skilled in the art should understand that the embodiments of the present invention described above and shown in the accompanying drawings are only examples and do not limit the present invention. The purpose of the present invention has been fully and effectively achieved. The functions and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.
Claims
1. A composite catalyst, characterized in that: The main components of the composite catalyst include: A metal catalyst, accounting for 5-15% of the mass of the composite catalyst, wherein the metal catalyst is at least one of a cobalt salt and a copper salt; Molecular sieves, accounting for 20-40% of the composite catalyst mass; Hydrogen peroxide, accounting for 5-15% of the mass of the composite catalyst, acts as an oxidant to provide a source of free radicals; Cross-linking agent, accounting for 10-30% of the composite catalyst mass; Synergistic promoter, accounting for 10-20% of the composite catalyst mass; The preparation process of the composite catalyst comprises the following steps: Step 1: dissolving the metal catalyst in an appropriate amount of water, stirring evenly, adding hydrogen peroxide, and controlling the temperature of the solution to be stirred at 30-40° C.; Step 2: Add molecular sieves to the solution and continue stirring to mix the molecular sieves evenly; Step 3: Slowly add the crosslinking agent to the solution and stir evenly; Step 4: adding a synergist to the solution; Step 5: heating the composite catalyst solution to 60-70° C. to activate the active sites of the catalyst; Step 6: Store the activated composite catalyst solution in a dry environment and under refrigerated conditions.
2. The composite catalyst according to claim 1, characterized in that: The molecular sieve is a ZSM-5 molecular sieve, and the particle size thereof is 1 nm to 5 nm.
3. The composite catalyst according to claim 1, characterized in that: The cobalt salt is cobalt chloride, and the copper salt is copper chloride.
4. The composite catalyst according to claim 1, characterized in that: The cross-linking agent is trivinyl triazine, and the synergistic accelerator is one of aluminum fluoride and ammonium bicarbonate.
5. A process for preparing an acrylic resin retanning agent using the composite catalyst as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Prepare a monomer solution by mixing acrylic acid, methacrylic acid and acrylamide monomers in proportion, and add an appropriate amount of water to the mixed solution; Step 2: adding the prepared composite catalyst to the monomer solution; Step 3: heating the reaction solution to 60-70°C and carrying out polymerization reaction under stirring, the reaction temperature is controlled below 90°C, and the reaction time is about 4 hours; Step 4: After the polymerization is completed, cool down to 40°C, add 30% sodium hydroxide solution for neutralization reaction, and adjust the pH value to 6.5-7.
0.
6. The process for preparing an acrylic resin retanning agent according to claim 5, characterized in that: In step 1, the ratio of acrylic acid, methacrylic acid and acrylamide monomers is: 60-70% acrylic acid, 20-30% methacrylic acid and 10-20% acrylamide.
7. The process for preparing an acrylic resin retanning agent according to claim 5, characterized in that: In step 2, the added amount of the composite catalyst is 0.5%-2% of the monomer mass.
Citation Information
Patent Citations
Polysaccharide and / or polypeptide based graft polymers as synthetic tannins
CN109265610A
Preparation of polymers by emulsion polymerization
CN1156727A
Ultrahigh-molecular-weight high-temperature-resistant and high-salt-resistant anionic polymer and preparation method thereof
CN117209661A
Ultrahigh-temperature-resistant seawater-based integrated fracturing fluid and preparation method thereof
CN117431052A